Identification of the building blocks of ventricular septation in monitor lizards (Varanidae) - Hanemaaijer, Jermo; Gregorovicova, Martina; Nielsen, Jan M; Moorman, Antoon F M; Wang, Tobias; Planken, R Nils; Christoffels, Vincent M; Sedmera, David; Jensen, Bjarke (Development, 2019)
Among lizards, only monitor lizards (Varanidae) have a functionally divided cardiac ventricle. The division results from the combined function of three partial septa, which may be homologous to the ventricular septum of mammals and archosaurs. We show in developing monitors that two septa, the 'muscular ridge' and 'bulbuslamelle', express the evolutionarily conserved transcription factors Tbx5, Irx1 and Irx2, orthologues of which mark the mammalian ventricular septum. Compaction of embryonic trabeculae contributes to the formation of these septa. The septa are positioned, however, to the right of the atrioventricular junction and they do not participate in the separation of incoming atrial blood streams. That separation is accomplished by the 'vertical septum', which expresses Tbx3 and Tbx5 and orchestrates the formation of the electrical conduction axis embedded in the ventricular septum. These expression patterns are more pronounced in monitors than in other lizards, and are associated with a deep electrical activation near the vertical septum, in contrast to the primitive base-to-apex activation of other lizards. We conclude that evolutionarily conserved transcriptional programmes may underlie the formation of the ventricular septa of monitors.
Keywords: Echocardiography; vývojová regulace genové exprese; Heart Atria; Evolution, Molecular; srdeční komory; těžké řetězce myosinu; zvířata; Embryo, Nonmammalian; embryo nesavčí; srdeční síně; T-Box Domain Proteins; Myosin Heavy Chains; Heart Ventricles; Time-Lapse Imaging; Lizards; molekulární evoluce; ještěři; mezikomorová přepážka; Homeodomain Proteins; Animals; časosběrné zobrazování; homeodoménové proteiny; Ventricular Septum; proteiny T-boxu; echokardiografie; Gene Expression Regulation, Developmental